Determination of bacterial endotoxins in parenteral solutions produced on a small scale in a clinical hospital - Renata Bozhinovska Popovska; Tatjana Gjurichikj; Branislava Janeva; Jelena Acevska; Aneta Dimitrovska (Makedonsko Farmacevtski Bilten)
Two different limulus amoebocyte lysate assays of bacterial endotoxins in parenteral solutions produced on a small scale in a clinical hospital are evaluated. The gel-clot LAL method and turbidimetric kinetic method were applied as techniques for determination of endotoxin from Gram – negative bacteria in a large volume of 0.9% NaCl solution for infusion. The same principle is applied but using different official methods for determination of bacterial endotoxin′s concertation. An overview of the advantages and disadvantages to the implementation of both methods is provided, with a detailed description of the procedures, comparison of the suitability of each method and recommendations based on the findings. The conventional gel-clot LAL method as a simple method can be recommended due to its economic sustainability in terms of equipment. On the other hand, the turbidimetric kinetic assay offers distinct advantages such as enhanced sensitivity, quantitative analysis capability, and instrumental reading. Furthermore, this method helps eliminate potential human variability in endpoint assessments. Therefore, the obtained results and critical aspects of the applied methods: the gel-clot LAL method and the turbidimetric kinetic method indicate that both LAL methods can be used for the determination of bacterial endotoxins in parenteral solutions, produced on a small scale and provide an opportunity for small laboratories to facilitate the decision – making process for choosing a method that best meets their requirements and resources.